Preparation and characterization of magnetic biosorbent based on oil palm empty fruit bunch fibers, cellulose and Ceiba pentandra for heavy metal ions removal - Daneshfozoun, S. (Elsevier B.V., 2017)
This study prepared, characterized and developed agro-based magnetic biosorbents (AMBs) from Ceiba pentandra (RKF), oil palm empty fruit bunches (EFB) and celluloses (CEL) extracted from EFB, using a novel, simple and cost-effective preparation technique for the removal of Pb(II), Cu(II), Zn(II), Mn(II) and Ni(II) ions from aqueous solutions. There has been no report on the methods to prepare and the use of magnetic biosorbent based on these biomaterials. The morphological, chemical and magnetic characterization suggested successful preparation of AMBs with good dispersion of magnetic nanoparticles on the surface of the base materials with clear magnetic properties. Optimum sorption was achieved between pH 5–7, and increase in initial ion concentration and solution temperature resulted in increased ion uptake. AMBs regeneration was successfully performed for 5 adsorption/desorption cycles. The magnetic biosorbent based on kapok showed the best Pb(II) removal efficiency of 99.4 and 49 mg/g adsorption capacity compared to 98.2 for cellulose and 97.7 for EFB. The magnetic biosorbents exhibited 10.3 higher removal efficiency than the raw sorbents. © 2017 Elsevier B.V.